Archery The ultimate resource for recurve and compound archers (Human Kinetics, 2013)
A guide for any archer wishing to improve their accuracy, increase consistency and achieve competitive success. Featuring the in-depth instruction, insight and advice from the world's top coaches and archers, it is suitable for those who compete with the recurve or compound bow